Gender-specific response to isoflurane preconditioning in focal cerebral ischemia - Kitano, Hideto (2007)
Inhalation anesthetics are effective chemical preconditioning agents in experimental cerebral ischemia. However, previous work has been performed exclusively in male animals. We determined if there is a gender difference in ischemic outcome after isoflurane preconditioning (IsoPC), and if this sex-specific response is linked to differences in Akt phosphorylation or expression of neuronal inducible cell-death putative kinase (NIPK), a negative modulator of Akt activation. Young and middle-aged male and female mice were preconditioned for 4 h with air (sham PC) or 1.0% IsoPC and recovered for 24 h. Cortices were subdissected from preconditioned young male and female mice for measurement of Akt phosphorylation (Western blot) and NIPK mRNA (quantitative polymerase chain reaction). Additional cohorts underwent 2 h of reversible middle cerebral artery occlusion. Lastly, male and female Akt1(+/+) and Akt1(−/−) mice were studied to determine if gender differences in ischemic outcome after IsoPC is Akt1-dependent. Infarction volume was determined at 22 h reperfusion (2,3,5-triphenyltetrazolium chloride). As expected, IsoPC decreased ischemic damage as compared with sham PC in young and middle-aged male mice. In contrast, IsoPC markedly increased infarction in young female mice and had no effect in middle-aged female mice. Cortical phospho-Akt was increased by IsoPC versus sham PC only in male mice. No increase was observed in IsoPC female mice. NIPK mRNA was higher in female mice than in male mice regardless of preconditioning status. Male IsoPC neuroprotection was lost in Akt1-deficient male mice. We conclude that IsoPC is beneficial only in ischemic male brain and that sex differences in IsoPC are mediated through Akt activation and basal NIPK expression.